Kontribusi Supervisi Akademik, Kompetensi Manajerial Kepala Sekolah, dan Etos Kerja Terhadap Kinerja Guru SMK Duta Bangsa Denpasar di Era Management Industri 4.0 - I.W.E. Purwanta; K.R. Dantes; I.G.K.R. Sunu (Jurnal Administrasi Pendidikan Indonesia, 2021)
This examination intends to decide the commitment of scholarly oversight, head administrative skill and hard working attitude to the exhibition of SMK Duta Bangsa instructors. This examination is an "ex-post facto" concentrate with an absolute example of 35 individuals. Information was gathered through polls and documentation. Information investigation was performed utilizing straightforward relapse strategies, different relapse and fractional relationship. The outcomes show that: (1) there is a critical commitment of scholarly oversight to instructor execution (2) there is a huge commitment of head administrative ability to educator execution (3) there is a huge commitment of hard working attitude to educator execution (4) together there is a huge commitment There is a huge connection between scholastic management, head administrative skill, and hard working attitude on the exhibition of SMK Duta Bangsa instructors. Accordingly, these three factors are utilized as indicators of the degree of propensity to expand the presentation of SMK Duta Bangsa educators in the modern administration time 4.0.